2016
DOI: 10.1016/j.mayocp.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Injection Technique Questionnaire Study

Abstract: From February 1, 2014, through June 30, 2015, 13,289 insulin-injecting patients from 423 centers in 42 countries took part in one of the largest surveys ever performed in diabetes. The goal was to assess patient characteristics, as well as historical and practical aspects of their injection technique. Results show that 4- and 8-mm needle lengths are each used by nearly 30% of patients and 5- and 6-mm needles each by approximately 20%. Higher consumption of insulin (as measured by total daily dose) is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 51 publications
0
77
0
3
Order By: Relevance
“…IM injections are a major risk factor for hypoglycemic events, including the unexpected sort which can lead to accidents, third-party interventions, hospitalization, and possible long-term morbidity [15]. These rates of 4-mm needle usage should also be put into context and compared to the overall findings in the ITQ, where roughly 29% of all patients (93% adult) were described by nurses as using the 4-mm needle, a percentage that is much lower than that reported in pediatric patients [3]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IM injections are a major risk factor for hypoglycemic events, including the unexpected sort which can lead to accidents, third-party interventions, hospitalization, and possible long-term morbidity [15]. These rates of 4-mm needle usage should also be put into context and compared to the overall findings in the ITQ, where roughly 29% of all patients (93% adult) were described by nurses as using the 4-mm needle, a percentage that is much lower than that reported in pediatric patients [3]. …”
Section: Discussionmentioning
confidence: 99%
“…The FIT (Forum for Injection Technique) recommendations released in 2009 and national guidelines from the UK, Ireland, China, Canada, Switzerland, India, and South Africa are evidence of this welcome development [27, 28]. Newer evidence based on the ITQ [3, 4] led to the publication of the New Insulin Delivery Recommendations in 2016 [5]. This international effort was followed by national recommendations in many countries, including India [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large worldwide survey comprising over 13,000 patients, higher numbers (56.5%) of participants were on insulin, while 40.5% of participants took both insulin and OADs, and minimal numbers used other drugs. [21] Metformin was the highest prescribed OAD (42.65%) which is, however, little less then expected, given that we included only T2DM patients on insulin. Surprisingly, substantial numbers of patients still received SUs in spite of their long duration of diabetes and concomitant insulin prescription indicating its popularity among primary and secondary level practitioners, even at the risk of causing more hypoglycemia.…”
Section: Discussionmentioning
confidence: 98%
“…[12] Data from a recent large worldwide survey indicated that insulin pen alone was used by 85.6% of patients, while 9.6% used a syringe alone, 2.8% used both, and 1.4% used a pen and another device (usually an insulin pump). [21] Thus, it seems economic condition is a important, but not the sole factor responsible for physicians'/patients' choice and familiarity in using modern devices during insulin therapy.…”
Section: Discussionmentioning
confidence: 99%